Pharmacokinetics and metabolism of an intravenously administered penem (Sch 34343) in humans. - Lin, C C (1987)
The pharmacokinetics of Sch 34343, a new broad-spectrum penem antibiotic, was studied in subjects receiving 1 g of 14C-labeled drug by intravenous administration. At the end of a 30-min intravenous infusion, the mean maximum concentration of drug in serum was 39 micrograms/ml for unchanged Sch 34343 and 49 mu eq/ml for total radioactivity. The mean serum half-lives of Sch 34343 were 0.16 h for the distribution phase and 0.80 h for the elimination phase. The total body clearance of Sch 34343 was 7.52 ml/min per kg, and the mean apparent volume of distribution was 525 ml/kg. Over a 4-day period, mean urinary excretion of radioactivity accounted for 87.9% of the dose, and mean urinary excretion of unchanged Sch 34343 accounted for 23.6% of the dose. The total radioactivity in feces on days 0 to 6 accounted for only 0.8% of the dose. In serum from 0.5 and 1 h, unchanged Sch 34343 represented the major radioactive peak, with negligible amounts of several metabolites. In urine, there were at least six metabolites in addition to Sch 34343. The amount of unchanged Sch 34343 accounted for 33% of radioactivity in samples of urine from 0 to 2 h, 22% in urine from 2 to 4 h, 15% in urine from 4 to 8 h, and 0% in urine from 8 to 12 h.